AGRICULTURAL PRODUCTIVITY TRENDS IN INDIA - ITS FUTURE PROSPECTS (International Journal of Food and Nutritional Sciences, 2022)
Agricultural productivity in India has seen significant changes over the years and continues tobe a topic of great importance. Several factors influence these trends, and the future prospectsdepend on various dynamics, including government policies, technological advancements,climate change, and market conditions.